2022
DOI: 10.1007/s11130-022-00993-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Properties of Bread Formulated with Plant-based Functional Ingredients Before Consumption and Possible Links with Health Outcomes After Consumption- A Review

Abstract: Bread is a commonly consumed staple and could be a viable medium to deliver plant-based ingredients that demonstrate health effects. This review brings together published evidence on the bioactive properties of bread formulated with plant-based ingredients. Health effects associated with the consumption of bread formulated with plant-based functional ingredients was also reviewed. Bioactive properties demonstrated by the functional ingredients fruits and vegetables, legumes, nuts and tea incorporated into brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…It has been reported that the oil and bioactive component (phenolic, flavonoid, α‐linolenic acid) content of dough and the antioxidant properties of bread increase with crushed seeds added (Afzal et al ., 2016; de Lamo & Gomez, 2018). In most cases, the seed meal dose in equilibrium with the desired physicochemical properties is related to the reported concentration of bioactive compounds in bread (Amoah et al ., 2022). In many countries, poppy seeds are used as the main ingredient in confectionery and pastry (Küsmenoğlu et al ., 2002; Swieca et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the oil and bioactive component (phenolic, flavonoid, α‐linolenic acid) content of dough and the antioxidant properties of bread increase with crushed seeds added (Afzal et al ., 2016; de Lamo & Gomez, 2018). In most cases, the seed meal dose in equilibrium with the desired physicochemical properties is related to the reported concentration of bioactive compounds in bread (Amoah et al ., 2022). In many countries, poppy seeds are used as the main ingredient in confectionery and pastry (Küsmenoğlu et al ., 2002; Swieca et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of bread with vegetables can increase the nutrient density of certain important nutrients including carotenoids (Ranawana et al, 2016 ). The addition of vegetables and seeds to frequently consumed foods as part of recipe development improves the quantity of bioactive nutrients, particularly the carotenoid concentration, increases variety, and has the potential to demonstrate health‐promoting benefits (Amoah et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…concentration, increases variety, and has the potential to demonstrate health-promoting benefits (Amoah et al, 2022).…”
mentioning
confidence: 99%
“…Among these products, bread stands out as the most widely consumed wheat‐based item worldwide. However, low protein flour not only creates nutritional challenges, but also does not suit for making good quality bread 1 . The reduction in protein content could be a result of an elevated CO 2 concentration 2 because wheat has a long growth cycle and is very vulnerable to extreme weather and climate events 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, low protein flour not only creates nutritional challenges, but also does not suit for making good quality bread. 1 The reduction in protein content could be a result of an elevated CO 2 concentration 2 because wheat has a long growth cycle and is very vulnerable to extreme weather and climate events. 3 In developing countries, factors such as cultivation practices, storage conditions, weak infrastructure and less advanced breeding programs, in addition to climate variation, have further restrained the wheat industry with respect to achieving desired quality flour and providing high quality products.…”
Section: Introductionmentioning
confidence: 99%